Chestnut blight in Portugal: Development of experimental control measures for integrated protection - Santos, Natércia (2004)
During the last decade it was observed an increase of chestnut mortality rates in Portugal, mainly in Trás-os-Montes, the most important chestnut area in the country. Several studies confirmed that mortality is due, among other causes, to "chestnut blight" caused by Cryphonectria parasitica. The validation of available technical and scientific knowledge on disease control measures, mainly preventive ones, depends on the experimental development. Thus, this project was implemented with the scope of developing field experiments in order to give continuity to ongoing and conc1uded research projects. A program including three main group of actions, based on previously obtained knowledge, was made, comprising: evaluation under field conditions of chestnut clones behaviour (selected under nursery environment in accordance with their pathogen tolerance); effect of preventive control measures on disease incidence (phytochemical control); new data for implementation of a biological control program (sample collection and vegetative compatible vc characterization of isolates, monitoring of the natural dispersion of vc groups from a focal point).